Three‐dimensional exoscope‐assisted single‐stage tracheal resection. Issue 12 (6th September 2022) - Pirola, Francesca; Mercante, Giuseppe; Russo, Elena; Giannitto, Caterina; Malvezzi, Luca; Ferreli, Fabio; Spriano, Giuseppe; Cariboni, Umberto; De Virgilio, Armando
Abstract: The three‐dimensional (3D) 4K exoscope is a surgical tool recently introduced in numerous fields of otolaryngology, such as microvascular surgery, otology, and laryngology. However, other surgical fields may also benefit from this technology. In this case, a single‐stage tracheal resection was planned with the aid of the 3D 4K exoscope, in a 75‐year‐old female with post‐tracheostomy tracheal stenosis. High‐quality magnification of the surgical field was obtained, with facilitated skeletonization of the laryngotracheal axis. The exoscope provided greater involvement in surgery and allowed more interactions among all operating room personnel and learners, as they could access the same field of view of the first surgeon, as well as perceiving depth of the surgical field with 3D technology. The exoscope represents a valid application in open surgery performed for laryngotracheal stenosis, with advantages of enhancing training and education, allowing precise surgical dissection, and reducing risks of iatrogenic damage to surrounding structures.